2013
DOI: 10.1159/000356034
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Acute Lung Injury and Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) is the most severe form of lung injury, characterised by alveolar oedema and vascular permeability, in part due to disruption of the alveolar capillary membrane integrity. Vascular endothelial growth factor (VEGF) was originally identified as a vascular permeability factor and has been implicated in the pathogenesis of acute lung injury/ARDS. This review describes our current knowledge of VEGF biology and summarises the literature investigating the potential role VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 129 publications
(182 reference statements)
1
61
0
1
Order By: Relevance
“…There are alterations in the plasma levels of VEGF, with associated falls in intrapulmonary levels seen in the early, exudative phase of lung injury; these changes normalise in recovery [34]. The observation that alveolar levels of VEGF are twice the level shown to induce angiogenesis [35], with restriction of these processes in healthy lung [36], leads to paradoxical and opposing views of the role of VEGF in normal and diseased lung [37,38]. It has been suggested that regulation of the biological activity of VEGF could provide an explanation of previous observations.…”
Section: Pathogenesis Of Ardsmentioning
confidence: 99%
“…There are alterations in the plasma levels of VEGF, with associated falls in intrapulmonary levels seen in the early, exudative phase of lung injury; these changes normalise in recovery [34]. The observation that alveolar levels of VEGF are twice the level shown to induce angiogenesis [35], with restriction of these processes in healthy lung [36], leads to paradoxical and opposing views of the role of VEGF in normal and diseased lung [37,38]. It has been suggested that regulation of the biological activity of VEGF could provide an explanation of previous observations.…”
Section: Pathogenesis Of Ardsmentioning
confidence: 99%
“…27 Since its discovery, VEGF has been implicated in a wide range of inflammatory diseases, including pulmonary inflammation, such as ARDS, VILI, fibrosis, and asthma. [28][29][30][31][32] While VEGF plays a critical role in organogenesis, 33,34 its expression in lungs persists into adulthood and remains the predominant source of VEGF in adults. 35,36 Given the physiological role played by VEGF in lung maintenance and homeostasis, the involvement of VEGF in the pathogenesis of ARDS has been well investigated.…”
mentioning
confidence: 99%
“…AT-II, and secreting surfactant protein (Barratt et al, 2014). VEGF also has chemotaxis ability to attract alveolar macrophages, which express VEGF receptor 2 (VEGFR2) (Clauss et al, 1996;Ferrara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%